A method for preparing zirconia ceramics having a glass penetration layer on the surface

By causing the tetragonal phase to single-climbing phase surface of zirconia ceramics to undergo a tetragonal phase transformation in a hydrothermal environment, and after the transformation, the glass penetrates into the cracks to form a dense surface, the problem of spontaneous phase transformation of ceramics in a hydrothermal environment is solved. , significantly improves its durability.

CN116606133BActive Publication Date: 2025-02-25SUZHOU CHENTAI MEDICAL INSTR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310344355.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2025-02-25
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

The existing Y-TZ tetragonal phase zirconia ceramics will spontaneously transform into a monoclinic phase under a hydrothermal environment of 100 to 400°C, resulting in changes in surface roughness and crack formation, limiting its application.

Method used

In the hydrothermal environment, place the tetragonal zirconia ceramics for a certain period of time, so that the surface of the tetragonal phase changes from the tetragonal phase to the monoclinal phase. After the transformation is completed, the glass penetrates into the cracks formed by the phase transformation, thereby forming a completely dense surface .

Benefits of technology

By forming a completely dense surface, external moisture is prevented from entering the inside of the ceramic and preventing internal phase transitions, thus obtaining zirconia ceramics with extremely excellent durability in hydrothermal environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004159039900000071
    Figure BDA0004159039900000071
  • Figure BDA0004159039900000081
    Figure BDA0004159039900000081
Patent Text Reader

Abstract

The present invention provides a method for preparing a zirconia ceramic having a glass permeation layer on the surface, the steps are as follows: pressing a zirconia powder containing 2.0-4.0mol% yttria to form a green body; placing the green body in a sintering furnace in an air atmosphere or a vacuum atmosphere, sintering at 1350-1500°C for 1-20 hours, and obtaining a tetragonal zirconia ceramic with a density ≥98% of the theoretical density; hydrothermally treating the tetragonal zirconia ceramic for 30 hours or more; mixing lanthanum-aluminum-silicon-boron glass powder with water to form a slurry, and evenly coating the surface of the zirconia ceramic after the hydrothermal treatment; placing the zirconia ceramic coated with the glass slurry in a sintering furnace, and keeping warm at 1100-1170°C for 1-4 hours, and obtaining a zirconia ceramic with a glass permeation layer on the surface. The zirconia ceramic of the present invention has a completely dense surface, effectively cutting off the way for external moisture to enter the interior of the zirconia ceramic, thereby obtaining a zirconia ceramic with extremely excellent durability in a hydrothermal environment and a glass permeation layer on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of zirconia ceramics, and in particular to a method for preparing zirconia ceramics with a glass penetration layer on the surface. Background Art

[0002] Zirconia ceramics have three crystal phases: monoclinic, tetragonal and cubic. When the tetragonal phase transforms into the monoclinic phase, it is not only accompanied by energy consumption, but also by a volume expansion of 3-5%. Volume expansion leads to the generation of compressive stress. The synergistic effect of this energy consumption and the formation of compressive stress effectively hinders the expansion of cracks, thereby significantly improving the fracture toughness of zirconia ceramics, making tetragonal zirconia ceramics have the reputation of "ceramic steel".

[0003] Pure zirconia exists in the monoclinic phase below 1170°C, in the tetragonal phase between 1170 and 2370°C, and in the cubic phase above 2370°C. Therefore, in order to obtain tetragonal zirconia ceramics at room temperature, stabilizers are often added to zirconia ceramics so that the tetragonal phase can be maintained at room temperature. Common stabilizers include Y2O3, CeO2, MgO, etc. Among them, Y2O3-stabilized tetragonal zirconia ceramics (hereinafter referred to as "Y-TZ") have been the most widely used due to their extremely high fracture strength and fracture toughness.

[0004] With the development of science and technology, people have further discovered that the existing Y-TZ tetragonal zirconia ceramics will spontaneously transform into a monoclinic phase in a hydrothermal environment of 100-400°C. This spontaneous phase change will not only cause submicron cracks in the zirconia ceramics, but also cause the surface roughness of the zirconia ceramics to change due to the 3-5% volume change associated with the phase change. This phenomenon limits the further application of 3Y-TZ tetragonal zirconia ceramics.

[0005] In order to solve this problem, researchers represented by CeramTec in Germany developed alumina-zirconia ceramics, in which zirconia is a minor component with a content of about 15wt%, which not only takes advantage of its phase change toughening, but also takes advantage of the pinning effect of the main component, the alumina matrix, to prevent the spontaneous phase change of zirconia in a hydrothermal environment. This idea has achieved certain results, but actual use experience shows that the spontaneous phase change of zirconia still exists.

[0006] CN115304371A is a solution proposed by the applicant, which is to infiltrate glass on the surface of sintered dense zirconia ceramics so that glass can enter the grain boundaries, cracks or pores on the ceramic surface, thereby preventing water molecules from entering the interior of the ceramic through these surface defects. This can effectively delay the spontaneous phase change of zirconia ceramics, and no new monoclinic phase is generated after 20 hours of hydrothermal treatment. However, when water molecules contact the grains on the surface for a long enough time, the phase change of the surface grains will still be triggered, such as a new monoclinic phase will be generated after 30 hours of hydrothermal treatment. This phase change will lead to the formation of cracks, and water molecules will penetrate into the interior of the ceramic along these cracks, thereby contacting the internal grains, causing these internal grains to also undergo phase changes one after another.

[0007] In order to overcome this deficiency, the present invention takes a different approach. It utilizes the characteristics that although tetragonal zirconia ceramics will undergo a phase transition from tetragonal phase to monoclinic phase in a hydrothermal environment, the phase transition will reach equilibrium. The sintered dense tetragonal zirconia ceramics are creatively placed in a hydrothermal environment for a certain period of time to allow the surface to fully undergo a transition from tetragonal phase to monoclinic phase. After the phase transition is completed, the glass is infiltrated into the cracks formed by the phase transition, thereby forming a completely dense surface. In the subsequent formal use process, on the one hand, since the surface has been hydrothermally treated, the transition from tetragonal phase to monoclinic phase has reached saturation, so the transition from tetragonal phase to monoclinic phase will no longer occur, and cracks will no longer form; on the other hand, the completely dense surface cuts off the path for water to enter the interior of the zirconia ceramic, preventing the zirconia ceramic from undergoing a phase transition when the ceramic is used in a hydrothermal environment, thereby obtaining a zirconia ceramic with extremely excellent durability in a hydrothermal environment and a glass penetration layer on the surface. Summary of the invention

[0008] Technical problem to be solved: The purpose of the present invention is to provide a method for preparing zirconia ceramics with a glass penetration layer on the surface, wherein the zirconia ceramics are placed in a hydrothermal environment for a period of time to allow the surface to fully undergo a transformation from a tetragonal phase to a monoclinic phase, and after the phase transformation is completed, the glass is infiltrated into the cracks formed by the phase transformation, thereby forming a completely dense surface, which has extremely excellent resistance to hydrothermal aging phase transformation.

[0009] Technical solution: A method for preparing a zirconia ceramic having a glass penetration layer on the surface, comprising the following steps:

[0010] (1) pressing zirconium oxide powder containing 2.0 to 4.0 mol % of yttria to form a green body;

[0011] (2) placing the green body in a sintering furnace in an air atmosphere or a vacuum atmosphere, and sintering at 1350 to 1500° C. for 1 to 20 hours to obtain a tetragonal zirconia ceramic having a density ≥ 98% of the theoretical density;

[0012] (3) hydrothermally treating the tetragonal zirconia ceramic for 30 hours or more;

[0013] (4) mixing lanthanum-aluminum-silicon-boron glass powder with water to form a slurry, and evenly coating the slurry on the surface of the hydrothermally treated zirconia ceramic;

[0014] (5) The zirconia ceramic coated with the glass slurry is placed in a sintering furnace and kept at 1100-1170° C. for 1-4 hours to obtain a zirconia ceramic with a glass penetration layer on the surface.

[0015] Furthermore, the pressing in step (1) is cold isostatic pressing at a pressure of 150 to 250 MPa.

[0016] Furthermore, the pressing in step (1) is performed by dry pressing at a pressure of 30 to 100 MPa, and then cold isostatic pressing at a pressure of 150 to 250 MPa.

[0017] Furthermore, the hydrothermal treatment time in step (3) is 30 to 60 hours, preferably 30 to 40 hours.

[0018] Furthermore, the content of yttrium oxide in step (1) is 3.0 mol%.

[0019] Furthermore, the zirconium oxide powder in step (1) also contains 0.15-0.35 wt% of aluminum oxide.

[0020] Furthermore, the zirconium oxide powder in step (1) also contains 0.20-0.25 wt% of aluminum oxide.

[0021] Furthermore, in step (4), the lanthanum-aluminum-silicon-boron glass contains 40wt% La2O3, 18wt% Al2O3, 20wt% SiO2, 19wt% B2O3 and the balance CaO.

[0022] Furthermore, the zirconia ceramic prepared by the above preparation method has a glass penetration layer on the surface.

[0023] Beneficial effects: The present invention has the following advantages:

[0024] 1. The present invention utilizes the characteristic that tetragonal zirconia ceramics will reach a phase transition equilibrium from tetragonal phase to monoclinic phase in a hydrothermal environment, and creatively places the sintered dense tetragonal zirconia ceramics in a hydrothermal environment for a certain period of time to allow the surface to fully undergo a transformation from tetragonal phase to monoclinic phase. After the phase transition is completed, glass is infiltrated into the cracks formed by the phase transition, thereby forming a completely dense surface of the zirconia ceramics.

[0025] 2. The zirconia ceramic with a glass penetration layer of the present invention has a completely dense surface, which can effectively cut off the path of external moisture entering the interior of the zirconia ceramic, and prevent the zirconia ceramic from undergoing a phase change when used in a hydrothermal environment, thereby obtaining a zirconia ceramic with a glass penetration layer on the surface that has extremely excellent durability in a hydrothermal environment.

[0026] The zirconia ceramics of the present invention can be used for semiconductors, medical treatment and other industrial applications.

[0027] In nature, hafnium (Hf) and zirconium elements exist in the form of solid solution and are difficult to separate. Therefore, in this application, "zirconium oxide (ZrO2)" contains ≤5wt% hafnium oxide.

[0028] In the present application, "hydrothermal treatment" refers to exposure to water vapor at a temperature of 134°C and a pressure of 0.2 MPa in an autoclave. In the present application, "vol%" refers to volume percentage, "wt%" refers to mass percentage, and "mol%" refers to molar percentage.

[0029] In the present application, X-ray diffraction analysis (abbreviated as "XRD", Cukα, 30KV, 15mA) is used to determine the crystalline phase content. Therefore, the obtained crystalline phase content refers to the crystalline phase content in the surface layer penetrated by the X-ray in the XRD analysis.

[0030] In the present application, room temperature refers to -20°C to 40°C.

[0031] In this application, the density of zirconia ceramics is measured using the water displacement method specified in GB / T 25995. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments:

[0033] Example 1 Preparation of zirconia ceramics and hydrothermal treatment

[0034] Take 400 grams of commercially available tetragonal zirconium oxide granulated powder containing 3 mol% yttrium oxide and an average particle size of 50 microns, dry-press under 50 MPa pressure, and then heat to 1400°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and keep warm for 2 hours. After cooling to 600°C at a rate of 2°C / min and furnace cooling to room temperature, a zirconium oxide ceramic with a density of 98.5% of the theoretical density is obtained, numbered ZR-01. The ceramic block ZR-01 is cut into 20 samples with a length of 10 mm, a width of 10 mm, and a height of 10 mm. One sample is randomly taken out, and the crystal phase composition of the zirconium oxide ceramic is analyzed by X-ray diffraction, and it is found that it contains 99.2 vol% of tetragonal zirconium oxide and 0.8 vol% of monoclinic zirconium oxide; under SEM (scanning electron microscope), the grain size of zirconium oxide in the zirconium oxide ceramic ZR-01 is 0.35 μm.

[0035] Three samples were randomly selected and hydrothermally treated in water vapor at 134°C at a pressure of 0.2 MPa for 20 hours. XRD and SEM analysis showed that the thickness of the surface phase change layer was 8 microns, and the contents of monoclinic and tetragonal zirconium oxide in the surface phase change layer were 18.2 vol% and 81.8 vol%, respectively.

[0036] Three samples were randomly selected and hydrothermally treated in water vapor at 134°C at a pressure of 0.2 MPa for 30 hours. XRD and SEM analysis revealed that the thickness of the surface phase change layer was 12 microns, and the contents of monoclinic and tetragonal zirconium oxide in the surface phase change layer were 27.2 vol% and 72.8 vol%, respectively.

[0037] Three samples were randomly selected and hydrothermally treated in water vapor at 134°C at a pressure of 0.2 MPa for 40 hours. XRD and SEM analysis revealed that the thickness of the surface phase change layer was 16 microns, and the contents of monoclinic and tetragonal zirconium oxide in the surface phase change layer were 27.2 vol% and 72.8 vol%, respectively.

[0038] This shows that after the zirconia ceramic ZR-01 is hydrothermally treated at 134°C and 0.2MPa pressure for 30 hours, the phase change will continue to penetrate deeper into the ceramic, but the hydrothermal phase change of the surface layer has reached saturation, and the content of tetragonal and monoclinic phases no longer changes.

[0039] Example 2 Preparation of zirconia ceramics and hydrothermal treatment

[0040] 400 g of commercially available tetragonal zirconium oxide granulated powder containing 3 mol% yttrium oxide and an average particle size of 50 microns was dry pressed at a pressure of 50 MPa, and then isostatically pressed at a pressure of 190 MPa, and then heated to 1500°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept at that temperature for 5 hours. After cooling to 600°C at a rate of 2°C / min and furnace cooling to room temperature, a dense zirconium oxide ceramic with a density of 99.0% of the theoretical density was obtained, which was numbered ZR-02.

[0041] The ceramic block ZR-02 was cut into 20 samples with a length of 10 mm, a width of 10 mm, and a height of 10 mm.

[0042] A sample was randomly taken out and the crystal phase composition of the zirconia ceramic was analyzed by X-ray diffraction. It was found that it contained 93.2 vol% tetragonal zirconia and 6.8 vol% monoclinic zirconia. Analysis under SEM (scanning electron microscope) showed that the grain size of zirconia in the zirconia ceramic ZR-02 was 0.55 μm.

[0043] Three samples were randomly selected and hydrothermally treated in water vapor at 134°C at a pressure of 0.2 MPa for 20 hours. XRD and SEM analysis revealed that the thickness of the surface phase change layer was 14 microns, and the contents of monoclinic and tetragonal zirconium oxide in the surface phase change layer zirconium oxide were 26.8 vol% and 73.2 vol%, respectively.

[0044] Three samples were randomly selected and hydrothermally treated in water vapor at 134°C at a pressure of 0.2 MPa for 30 hours. XRD and SEM analysis revealed that the thickness of the surface phase change layer was 20 microns, and the contents of monoclinic and tetragonal zirconium oxide in the surface phase change layer zirconium oxide were 34.6 vol% and 65.4 vol%, respectively.

[0045] Three samples were randomly selected and hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 40 hours. XRD and SEM analysis revealed that the thickness of the surface phase change layer was 25 μm, and the contents of monoclinic and tetragonal zirconium oxide in the surface phase change layer zirconium oxide were 34.6 vol% and 65.4 vol%, respectively.

[0046] This shows that after the zirconia ceramic ZR-02 is hydrothermally treated at 134°C and 0.2MPa pressure for 30 hours, the phase change will continue to penetrate deeper into the ceramic, but the hydrothermal phase change of the surface layer has reached saturation, and the content of tetragonal and monoclinic phases no longer changes.

[0047] Example 3 Preparation of zirconia ceramics and hydrothermal treatment

[0048] 400 grams of commercially available tetragonal zirconium oxide granulated powder containing 3 mol% yttrium oxide, 0.25 wt% Al2O3 and an average particle size of 60 microns were taken, dry pressed at a pressure of 50 MPa, and isostatically pressed at a pressure of 180 MPa, and then heated to 1350°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 10 hours. After cooling to 600°C at a rate of 2°C / min and furnace cooling to room temperature, a dense zirconium oxide ceramic with a density of 99.7% of the theoretical density was obtained, which was numbered ZR-03.

[0049] The ceramic block ZR-03 was cut into 20 samples with a length of 10 mm, a width of 10 mm, and a height of 10 mm.

[0050] A sample was randomly taken out and the crystal phase composition of the zirconia ceramic was analyzed by X-ray diffraction, which revealed that it contained 100 vol% tetragonal zirconia. Analysis under SEM (scanning electron microscope) showed that the grain size of zirconia in the zirconia ceramic ZR-03 was 0.28 μm.

[0051] Three samples were randomly selected and hydrothermally treated in water vapor at 134°C at a pressure of 0.2 MPa for 20 hours. XRD and SEM analysis revealed that the thickness of the surface phase change layer was 6 microns, and the contents of monoclinic and tetragonal zirconium oxide in the surface phase change layer zirconium oxide were 14.2 vol% and 85.8 vol%, respectively.

[0052] Three samples were randomly selected and hydrothermally treated in water vapor at 134°C at a pressure of 0.2 MPa for 30 hours. XRD and SEM analysis revealed that the thickness of the surface phase change layer was 10 microns, and the contents of monoclinic and tetragonal zirconium oxide in the surface phase change layer zirconium oxide were 24.7 vol% and 75.3 vol%, respectively.

[0053] Three samples were randomly selected and hydrothermally treated in water vapor at 134°C at a pressure of 0.2 MPa for 40 hours. XRD and SEM analysis revealed that the thickness of the surface phase change layer was 14 microns, and the contents of monoclinic and tetragonal zirconium oxide in the surface phase change layer zirconium oxide were 24.7 vol% and 75.3 vol%, respectively.

[0054] This shows that after the zirconia ceramic ZR-03 is hydrothermally treated at 134°C and 0.2MPa pressure for 30 hours, the phase change will continue to penetrate deeper into the ceramic, but the hydrothermal phase change of the surface layer has reached saturation, and the content of tetragonal and monoclinic phases no longer changes.

[0055] Example 4 Preparation of Lanthanum-Boron-Silicon-Aluminum Glass Powder

[0056] Chemically pure lanthanum oxide La2O3, aluminum oxide Al2O3, silicon oxide SiO2, boron oxide B2O3 and calcium oxide CaO powders were added with an appropriate amount of anhydrous ethanol in a mass ratio of 40:18:20:19:3, ball-milled for 4 hours, and then dried in an oven at 100°C. The dried powder was placed in a platinum crucible, melted in a sintering furnace at 1400°C for 3 hours, and then taken out at high temperature and directly poured into deionized water to obtain glass powder. The glass powder was placed in an agate ball mill, using zirconium oxide grinding balls, adding an appropriate amount of anhydrous ethanol, ball-milled for 24 hours, then poured into a porcelain plate, and dried in an oven at 100°C to obtain lanthanum-boron-silicon-aluminum glass powder.

[0057] Example 5 Preparation of glass-infiltrated zirconia ceramics

[0058] The 10 cut zirconia ceramic ZR-01 samples prepared in Example 1 were placed in an autoclave at a temperature of 134° C. and a pressure of 0.2 MPa and subjected to hydrothermal treatment for 30 hours.

[0059] Take 100 grams of the lanthanum-boron-silicon-aluminum glass powder prepared in Example 4, add an appropriate amount of deionized water, and prepare it into a paste. Use a brush to evenly apply it on all surfaces of 10 samples. Place the sample coated with the glass paste in a sintering furnace, heat it to 1120°C at a rate of 5°C / min, keep it warm for 2 hours, and then cool it to room temperature at a rate of 5°C / min. Take out the sample, and gently polish off the glass layer on the surface with 800-mesh sandpaper to obtain a glass-infiltrated zirconia ceramic sample, numbered ZR-01G.

[0060] Three ZR-01G samples were randomly selected and the grain size and distribution of glass phase were observed using backscattered electrons in a scanning electron microscope (SEM). It was found that the thickness of the phase change layer remained unchanged at 12 microns; the glass not only fully penetrated into the surface phase change layer of the zirconia ceramic, but also entered the 5-micron thickness area below the phase change layer, and the cracks formed by the previous phase change were filled with the glass phase. XRD analysis of the phase structure showed that the relative content of monoclinic and tetragonal zirconia remained unchanged, still 27.2vol% and 72.8vol%, respectively, the same as before the glass penetration.

[0061] Three ZR-01G samples were randomly taken out and hydrothermally treated in water vapor at 134°C for 60 hours at a pressure of 0.2 MPa. The phase structure was then analyzed by XRD and the microstructure was observed under SEM. It was found that the thickness of the original surface phase change layer did not change and was still 12 microns. No new cracks were formed. Moreover, the contents of monoclinic and tetragonal zirconium oxide did not change compared with before the hydrothermal treatment, which were 27.2 vol% and 72.8 vol%, respectively.

[0062] It can be seen that after the hydrothermal treatment for up to 60 hours, the zirconia ceramic ZR-01G with a surface glass infiltration layer of the present invention did not undergo hydrothermal aging phase transformation.

[0063] Example 6 Preparation of glass-infiltrated zirconia ceramics

[0064] The 10 cut zirconia ceramic ZR-02 samples prepared in Example 2 were placed in an autoclave at a temperature of 134° C. and a pressure of 0.2 MPa and subjected to hydrothermal treatment for 30 hours.

[0065] Take 100 grams of the lanthanum-boron-silicon-aluminum glass powder prepared in Example 4, add an appropriate amount of deionized water, and prepare it into a paste. Use a brush to evenly apply it on all surfaces of 10 specimens. Place the specimens coated with the glass paste in a sintering furnace, heat it to 1120°C at a rate of 5°C / min, keep it warm for 3 hours, and then cool it to room temperature at a rate of 5°C / min. Take out the specimens, and gently polish off the glass layer on the surface with 800-mesh sandpaper to obtain a glass-infiltrated zirconia ceramic specimen, numbered ZR-02G.

[0066] Three ZR-02G samples were randomly selected and the grain size and distribution of glass phase were observed by backscattered electrons in a scanning electron microscope (SEM). It was found that the thickness of the phase change layer remained unchanged, still 20 microns; the glass not only fully penetrated into the surface phase change layer of the zirconia ceramic, but also entered the 4-micron thickness area below the phase change layer, and the cracks formed by the previous phase change were filled with glass phase. XRD analysis of the phase structure showed that the relative contents of monoclinic and tetragonal zirconia remained unchanged, still 34.6vol% and 65.4vol%, respectively. Three ZR-02G samples were randomly selected and hydrothermally treated at 134℃ in water vapor at a pressure of 0.2MPa for 60 hours, then XRD analysis of the phase structure was performed and the microstructure was observed under SEM. It was found that the thickness of the original surface phase change layer did not change, still 20 microns, and no new cracks were formed, and the relative contents of monoclinic and tetragonal zirconia did not change compared with before the hydrothermal treatment, which were 34.6vol% and 65.4vol%, respectively.

[0067] It can be seen that after the hydrothermal treatment for up to 60 hours, the zirconia ceramic with the surface glass infiltration layer of the present invention did not undergo hydrothermal aging phase transformation.

[0068] Example 7 Preparation of glass-infiltrated zirconia ceramics

[0069] The 10 cut zirconia ceramic ZR-03 samples prepared in Example 3 were placed in an autoclave at a temperature of 134° C. and a pressure of 0.2 MPa for hydrothermal treatment for 30 hours.

[0070] Take 100 grams of the lanthanum-boron-silicon-aluminum glass powder prepared in Example 4, add an appropriate amount of deionized water, and prepare it into a paste. Use a brush to evenly apply it on all surfaces of 10 specimens. Place the specimens coated with the glass paste in a sintering furnace, heat it to 1120°C at a rate of 5°C / min, keep it warm for 4 hours, and then cool it to room temperature at a rate of 5°C / min. Take out the specimens, and gently polish off the glass layer on the surface with 800-mesh sandpaper to obtain a glass-infiltrated zirconia ceramic specimen, numbered ZR-03G.

[0071] Two samples were randomly selected and the grain size and distribution of glass phase were observed by backscattered electrons in a scanning electron microscope (SEM). It was found that the thickness of the phase change layer remained unchanged, still 10 microns; the glass not only fully penetrated into the surface phase change layer of the zirconia ceramic, but also entered the 2 micron thickness area below the phase change layer, and the cracks formed by the previous phase change were filled with the glass phase. XRD analysis of the phase structure showed that the relative content of monoclinic and tetragonal zirconia remained unchanged, still 24.7vol% and 75.3vol%, respectively.

[0072] Three ZR-03G samples were randomly taken out and hydrothermally treated in water vapor at 134°C for 60 hours at a pressure of 0.2 MPa. The phase structure was then analyzed by XRD and the microstructure was observed under SEM. It was found that the thickness of the original surface phase change layer did not change and was still 10 microns. No new cracks were formed, and the relative contents of monoclinic and tetragonal zirconia did not change compared with before this hydrothermal treatment, which were 24.7 vol% and 75.3 vol%, respectively.

[0073] It can be seen that after the hydrothermal treatment for up to 60 hours, the zirconia ceramic ZR-03G with a surface glass infiltration layer of the present invention did not undergo hydrothermal aging phase transformation.

[0074] The test results of the above embodiments are summarized in the following table.

[0075]

[0076]

[0077] Example 8 Preparation of Zirconia Ceramic Femoral Head Prosthesis with Glass Infiltration Layer

[0078] The process of Example 3 is adopted to prepare a zirconia ceramic femoral head prosthesis for hip replacement. The inner taper hole and outer spherical surface of the femoral head prosthesis are ground to the final size. 10 grams of lanthanum-boron-silicon-aluminum glass powder prepared in Example 4 are taken, and an appropriate amount of deionized water is added to be modulated into a paste. The femoral head prosthesis coated with glass paste is placed in a sintering furnace, heated to 1120°C at a rate of 5°C / minute, kept warm for 4 hours, and then cooled to room temperature at a rate of 5°C / minute. The femoral head prosthesis is taken out. The glass layer on the surface of the inner taper hole is gently polished off with 800-mesh sandpaper to obtain a glass-infiltrated zirconia ceramic femoral head prosthesis. After being implanted into the human body, the zirconia ceramic femoral head prosthesis with a surface glass infiltration layer of the present invention can be reasonably predicted to not undergo aging phase change and has a service life of more than 30 years.

[0079] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a zirconia ceramic having a glass penetration layer on the surface, characterized in that: The following steps are involved: (1) pressing zirconium oxide powder containing 2.0 to 4.0 mol % of yttria to form a green body; (2) placing the green body in a sintering furnace in an air atmosphere or a vacuum atmosphere, and sintering at 1350 to 1500° C. for 1 to 20 hours to obtain a tetragonal zirconia ceramic having a density ≥ 98% of the theoretical density; (3) hydrothermally treating the tetragonal zirconia ceramic for 30 hours or more; (4) mixing lanthanum-aluminum-silicon-boron glass powder with water to form a slurry, and evenly coating the slurry on the surface of the hydrothermally treated zirconia ceramic; (5) The zirconia ceramic coated with the glass slurry is placed in a sintering furnace and kept at 1100-1170° C. for 1-4 hours to obtain a zirconia ceramic with a glass penetration layer on the surface.

2. The method for preparing a zirconia ceramic having a glass permeation layer on the surface according to claim 1, characterized in that: The pressing molding in the step (1) is cold isostatic pressing at a pressure of 150 to 250 MPa.

3. The method for preparing a zirconia ceramic having a glass permeation layer on the surface according to claim 1, characterized in that: The pressing molding in step (1) is performed by dry pressing at a pressure of 30 to 100 MPa, and then cold isostatic pressing at a pressure of 150 to 250 MPa.

4. The method for preparing a zirconia ceramic having a glass permeation layer on the surface according to claim 1, characterized in that: The hydrothermal treatment time in step (3) is 30 to 40 hours.

5. The method for preparing a zirconia ceramic having a glass permeation layer on the surface according to claim 1, characterized in that: The content of yttrium oxide in the step (1) is 3.0 mol%.

6. The method for preparing a zirconia ceramic having a glass permeation layer on the surface according to claim 1, characterized in that: The zirconium oxide powder in step (1) also contains 0.15-0.35 wt% of aluminum oxide.

7. The method for preparing a zirconia ceramic having a glass permeation layer on the surface according to claim 1, characterized in that: The lanthanum-aluminum-silicon-boron glass in step (4) contains 40wt% La2O3, 18wt% Al2O3, 20wt% SiO2, 19wt% B2O3 and the balance CaO.

8. Zirconia ceramics having a glass permeation layer on the surface prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Glass-permeable zirconia ceramic and preparation method thereof

    CN115304371A